Ab initio COmputational Study of the Propesties of Octahedral Complex Between Iron (III) and N-benzoyl-N'-phenylthiourea Ligand using Hartree-Fock Method - KOYIMATU (NIM 10505076), MUHAMAD
N-benzoyl-N'-phenylthiourea (C14H12N2OS) has been synthesized recently by other researcher. Free electron pairs on N, S, and O atoms in this compound makes it possible be ligands in the formation of complex compounds with transition metal ions. Iron metal ion was considered as one of the candidates to form complex compounds with the ligand. This study aims to examine the possible complex structures that could be synthesized and to determine the properties of the complexes. Unrestricted-Hartree-Fock method with STO-3G basis set was used to determine the complex structure and 6-31G basis set was used to calculate energies and other properties. Computational calculation was performed using Xeon 2 processors and 10 processors cluster computer. The calculations show that a complex structure was formed by iron(III) and the ligand through bonds with S and O atoms. On the other way, iron(III) complex with the ligand via N atoms was not formed. It might be explained by the presence of steric hindrance in the complex. There was dehydrogenation reaction occurred before the bond formation between iron(III) and sulfur and oxygen atoms in the ligand in order to supply free electron pair from ligand to the central atom.